Pengaruh Motivasi Dan Gaya Hidup Terhadap Keputusan Pembelian Pada Singgah Kedai Kopi - Basita Ning Setyawati; Eko Boedhi Santoso (Jurnal Ekonomi dan Bisnis Digital, 2023)
This study aims to determine the effect of motivation and lifestyle on purchasing decisions at Singgah Kedai Kopi. This research was a quantitative study with an explanatory research approach. The method of collecting data was through a questionnaire given to 100 respondents who are consumers of Singgah Kedai Kopi. The sampling technique used in this study was non-probability sampling with accidental sampling method. Data analysis in this study used multiple regression analysis and hypothesis testing. The results of this study indicate that motivation and lifestyle partially and simultaneously have a positive and significant influence on purchasing decision at Singgah Kedai Kopi. The biggest influence on purchasing decisions is motivation.